Cysteine conjugates of acetaminophen and p-aminophenol are potent inducers of cellular impairment in human proximal tubular kidney HK-2 cells - Rousar, Tomas; Handl, Jiri; Capek, Jan; Nyvltova, Pavlina; Rousarova, Erika; Kubat, Miroslav; Smid, Lenka; Vanova, Jana; Malinak, David; Musilek, Kamil; Cesla, Petr (Archives of toxicology, 2023)
Acetaminophen (APAP) belong among the most used analgesics and antipyretics. It is structurally derived from p-aminophenol (PAP), a potent inducer of kidney toxicity. Both compounds can be metabolized to oxidation products and conjugated with glutathione. The glutathione-conjugates can be cleaved to provide cysteine conjugates considered as generally nontoxic. The aim of the present report was to synthesize and to purify both APAP- and PAP-cysteine conjugates and, as the first study at all, to evaluate their biological effects in human kidney HK-2 cells in comparison to parent compounds. HK-2 cells were treated with tested compounds (0-1000 μM) for up to 24 h. Cell viability, glutathione levels, ROS production and mitochondrial function were determined. After 24 h, we found that both APAP- and PAP-cysteine conjugates (1 mM) were capable to induce harmful cellular damage observed as a decrease of glutathione levels to 10% and 0%, respectively, compared to control cells. In addition, we detected the disappearance of mitochondrial membrane potential in these cells. In the case of PAP-cysteine, the extent of cellular impairment was comparable to that induced by PAP at similar doses. On the other hand, 1 mM APAP-cysteine induced even larger damage of HK-2 cells compared to 1 mM APAP after 6 or 24 h. We conclude that cysteine conjugates with aminophenol are potent inducers of oxidative stress causing significant injury in kidney cells. Thus, the harmful effects cysteine-aminophenolic conjugates ought to be considered in the description of APAP or PAP toxicity.
Keywords: aminofenoly; Kidney; Acetaminophen; lidé; cystein; paracetamol; glutathion; ledviny; Cysteine; Glutathione; Aminophenols; Humans